Influence of working environment, workload and job autonomy towards job stress: a case of casual dining restaurant employees in Klang Valley, Malaysia - Amran, Farah Wahida; Ghazali, Hazrina; Hashim, Saedahtinnur (Management Academic Research Society, 2019)
Work related stress is common in many industries and this situation troubling the organization due to lower productivity or poor performance. Stress at workplace is quite intense in restaurant industry because this industry required high commitments from employee. Employees are expected to work in shifts, long working hours, to have little or no weekend time, do repetitive work, to face with difficult customers, also to work within inefficient management. Even though study on job stress has widely done, but little studies were found on casual dining restaurant industry. Hence, the aim of this study is to determine the influence of workload towards job stress on employees in casual dining restaurant. The study was conducted at casual dining restaurants within Klang Valley area. The primary data of this study was derived from quantitative method and strictly to Malaysian employees only. The sample was all casual dining restaurant employees amounting to 620 people. Data were collected by using self-administered questionnaire. Then, the data were analyzed Statistical Package for the Social Sciences (SPSS) version 22. The results showed that workload have positive and significant influence on employee’s job stress at casual dining restaurant. Results also found that most of the respondents felt stress between 1-2 times in a week with 52.7% which equals to 327 of respondents. Findings from this study could suggest the casual dining operators and management to highlight factor that could contribute to job stress and strategize ways to minimize stress and ultimately retain their employees in the restaurant.